Prospects and consequences of migration in the Western Balkans - Люба, О. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The author considers the causes and features of the modern migration crisis in the Balkans. Attention is focused on the spontaneity, magnitude and the transitional nature of the contemporary waves of migration through the «Balkan corridor». The author concludes that the processes of the ethno-cultural and religious transformation of the European space are irreversible. The necessity of the reform of the European migration system and reformatting of the migration policies on the periphery of the European Union is underlined.